Incorporation of Eye Movement in Vehicle Dynamics and Auto Notification System - Venkatraman, S.; Balamurugan, C.; Karthikeyan, E.; Kishore, V.; Hariharan, R. (International Journal of Engineering and Technology, 2018)
Here vision based gradient derivative model is proposed to detect eye blink for fully automated vehicle control system. In addition, the proposed model also integrates tiny encrypted IR based codebook model for sending notifications to other vehicles in order to remotely forward their status. This system comprised of a simple pre-processing and feature extraction methods and requires no human intervention to reduce the false rate. It allows for prompt accessibility, efficient usage of vision input characteristics and provides user convenience. The aim of the work presented in this thesis is to make automatic vehicle control system and IR based signal reception codec to combat environmental differences